1 2 3
2 3 4
3 4 5
4 5 6
wait, there's a pattern here. does it work for all numbers?
x, x+1, x+2
(x+1)^2 (the middle number squared)
= x^2 + 2x + 1
product of first and third numbers =
x(x+2) = x^2 + 2x
which is always 1 less than
x^2 + 2x + 1.
does it also work for negative numbers?
let's try -5, -4, -3
-5 * -3 = 15
(-4)^2 = 16
seems to work. let's prove it.
for x > 0, let's examine -x-1, -x, -x+1.
(-x)^2 = x^2
(-x-1)(-x+1) = x^2 -x +x -1 = x^2 - 1,
one less than x^2, quod erat dictum.
how about if we cross zero?
-1, 0, 1
(-1)*1 = -1
0^2 = 0
yes, that works too!
2006-10-19 10:26:49
·
answer #1
·
answered by Glenn 2
·
1⤊
1⤋
This is actually true for *any* integers (even negative ones).
For example:
1, 2, 3:
1 * 3 = 3
2² - 1 = 4 - 1 = 3
99, 100, 101:
99 * 101 = 9999
100² - 1 = 10000 - 1 = 9999
-1, 0, 1:
-1 * 1 = -1
0 - 1 = -1
-5, -6, -7:
-5 * -7 = 35
(-6)² - 1 = 36 - 1 = 35
The reason is pretty obvious if you try to figure this out using algebra.
Let the numbers be:
x = first integer
x + 1 = second integer
x + 2 = third integer
So you are trying to find solutions for:
x (x + 2) = (x + 1)² - 1
Expanding out the left and right sides:
x² + 2x = x² + 2x + 1 - 1
Simplifying:
x² + 2x = x² + 2x
This is true for all values of x. So *any* set of consecutive integers will work.
The answer is as easy as 1-2-3!
2006-10-19 10:42:32
·
answer #2
·
answered by Puzzling 7
·
0⤊
1⤋
Suppose the three numbers are
n-1, n and n+1
(n-1)(n+1) = n^2 -1
This is true for any n.
So
three consecutive integers such that the first times the third is 1 less than
the second squared
is always true.
Th
2006-10-19 10:49:44
·
answer #3
·
answered by Thermo 6
·
0⤊
0⤋
This works with any three consecutive non-negative integers. Just choose any three numbers that are consecutive and at least zero.
4, 5, 6
4*6 = 24
5^2 = 25
11, 12, 13
11*13 = 143
12^2 = 144
Why does this work?
Let the three consecutive numbers be n-1, n, and n+1
The product of the first and the third is (n-1)(n+1).
If you multiply this out you get n^2 - 1, which is one less than n^2.
2006-10-19 10:29:21
·
answer #4
·
answered by Anonymous
·
0⤊
1⤋
What about 1,2,3? The first times the third 1*3=3 which is one less than the second squared 2^2=4-1=3.
2006-10-19 10:26:28
·
answer #5
·
answered by msi_cord 7
·
0⤊
1⤋
ANY three consecutive integers will work!! (Everyone until now has specified positive or non-negative. They work too.
{-3,-4,-5} : (-3)(-5) = (-4)^2 - 1; 15=15. In fact, it also works for any three REAL numbers that are 1 apart {π, π+1, π+2}. There is nothing in the proof that precludes negativity.)
Let them be x, x+1, and x+2
x(x+2) always equals (x+1)^2 - 1
Proof:
x(x+2) = x^2 + 2x
= x^2 + 2x + 1 - 1
= (x+1)^2 - 1
{1,2,3}
1*3 = 2^2 -1
{2,3,4}
2*4 = 3^2 -1
etc.!!!
2006-10-19 10:29:34
·
answer #6
·
answered by Scott R 6
·
0⤊
0⤋
The integers are x, x+1 and x+2.
So:
(x)(x+2) < (x+1)²
x² + 2x < x² + 2x + 1
Choose any positive integer and it will work.
ie. x = 1
1, 2, 3
1² + 2(2) = 5
1² + 2(2) + 1 = 6
And 5 is less than 6.
2006-10-19 10:28:32
·
answer #7
·
answered by Leah H 2
·
0⤊
1⤋
2 - 3 - 4.
2*4 EQUAL TO (3*3)-1 = 8.
2006-10-19 10:30:15
·
answer #8
·
answered by zolerino 2
·
0⤊
0⤋